The Expansion of Intensive Beef Farming to the Brazilian Amazon. (July 2019) - Vale, Petterson; Gibbs, Holly; Vale, Ricardo; Christie, Matthew; Florence, Eduardo; Munger, Jacob; Sabaini, Derquiane
Highlights: Intensive beef farming on rapid expansion into the Brazilian Amazon. Possible drivers: land scarcity coupled with rising demand for meat. Feedlots associated with higher productivity and less on-property deforestation. Feedlots also associated with more crop production in and outside cattle ranches. Potential negative effects: deforestation leakage, poor animal welfare, pollution. Abstract: Systems of intensive animal farming, such as the confinement of beef cattle, are widespread in the developed world. Such practices have been under scrutiny since the 1960s for animal welfare and pollution issues. Here, we document the expansion of intensive beef farming to the Brazilian Amazon in order to assess socio-environmental implications. Using a combination of data mining and field surveys, we developed a georeferenced dataset of 201 cattle confinements in the states of Mato Grosso (Cerrado and Amazon biomes), Pará and Rondônia (Amazon biome), collected in 2017. In Mato Grosso, the country's agribusiness powerhouse, confinements are well established and account for ˜20% of the cattle slaughter. But rapid expansion in Pará and Rondônia remains largely unnoticed due to the absence of data since 2012. We used the new dataset to map cattle confinements across space and time. For the first time, (1) we document an expansion to the Amazon biome; (2) we also show that confinements are associated with substantially higher productivity rates, though intensified pasture-based systems can reach comparable yields; (3) that confinements have crop production levels 2-3 times higher than comparable properties, both in- and out-of-farm; and (4) that confinements tend to slow down on-property deforestation when compared to fattening ranches in the Amazon biome, although off-property effects could be substantial and need further study. Overall, the implications of intensive beef farming for animal welfare and local waste generation in Brazil require attention as pressure to avoid deforestation continues to stimulate the practice.